DETERMINANTS FACTORS OF WORK STRESS AMONG NURSES IN PERFORMING SERVICES DURING THE COVID-19 PANDEMIC - Ni Putu Yesika Elvianasari; Ni Made Nopita Wati; Komang Ayu Mustriwati (POLTEKKES KEMENKES JAYAPURA, 2022)
The increasing number of Covid-19 cases has led to a high demand for health services and the number of health workers in hospitals. This results in health workers working with the intensity of long working hours and increasing workloads. The high demands of work and excessive worry are a source of stres for nurses. The purpose of this study was to determine the determinants of factors that were associated with and most related to the work stres of nurses in carrying out services during the Covid-19 pandemic in the intensive isolation room of the Bali Mandara Hospital. The research method used is descriptive quantitative with a cross-sectional approach. The sampling technique respondent in this study is a total sample of 129 nurses. The instrument used in this research is a job stres questionnaire. Data were analyzed using univariate analysis, bivariate analysis (Spearman Rank correlation test), and multivariate analysis (Regression test). The results showed that most of the subject were aged 31-40 years (74,4%), female (60,5%), unmarried status (51,95%), working period of 3-5 years (79,8%), has a Diploma (76,7%) and has mild work stres (81,4%). The results showed that there was a relationship between age (p=0,001), marital status (p=0,003), years of service (p=0,006) and education (p=0,000) with work stres. There is no relationship between gender (p=0,108) and work stres. The results also showed that the level of education is the most related factor to the work stres of nurses. Ti is expected for nurses to continue their studies to a higher level so that nurses have broad insight and are not easily stresed when experiencing obstacles at work. Keywords: Covid-19, Job stres, Nurses